2013
DOI: 10.1177/1948550613499942
|View full text |Cite
|
Sign up to set email alerts
|

“€14,875?!”: Precision Boosts the Anchoring Potency of First Offers

Abstract: In negotiations, higher first offers from sellers drive up sale prices—reversely, buyers benefit from lower first offers. Whereas abundant research has replicated this robust anchoring effect of opening offers, little is known about the impact of anchors’ precision or the interplay of extremity and precision. We propose that precision moderates the effect of anchor extremity, in that precise anchors gain in plausibility and thereby magnify the first-mover advantage. Two experiments tested this assumption. Stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 37 publications
6
42
1
Order By: Relevance
“…Whenever respondents are presented with a precise, rather than a rounded number, their stated preferences end up closer to that number. This finding aligns well with previous studies on the price precision effect (e.g., Loschelder et al ). However, using precise numbers had no significant effect on the respondents’ perception of the sender’s seriousness and knowledge.…”
Section: General Conclusion and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Whenever respondents are presented with a precise, rather than a rounded number, their stated preferences end up closer to that number. This finding aligns well with previous studies on the price precision effect (e.g., Loschelder et al ). However, using precise numbers had no significant effect on the respondents’ perception of the sender’s seriousness and knowledge.…”
Section: General Conclusion and Discussionsupporting
confidence: 93%
“…Substantially, these numbers differ by approximately just 1 percent, and one could argue that such a small difference is unimportant from a policy perspective. However, several studies on the psychology of negotiations and appraising suggest that the difference in precision may have an effect on how voters respond to these numbers because precise numbers serve as stronger anchors than round numbers (Loschelder et al ). For example, real estate listed with a precise list price tends to sell at a price closer to this list price than real estate listed with a round price (Janiszewski & Uy ; Thomas et al ).…”
Section: From Perceptions and Attitudes To Pecuniary Answersmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the participants' numeric estimation was affected by the anchor, the roulette ball number. Later studies also confirmed the effect of an anchoring (Hess & Orbe 2013;Loschelder, Stuppi, & Trötschel, 2013;Clepce, Neumann, Martus, Nitsch, Wielopolski, Koch, Kornhuber, Reich, & Thuerauf, 2014). That is to say, when people try to answer a question that they do not know the answer to, they tend to be affected either consciously or subconsciously by the anchor, which is not related to the question.…”
Section: Theoretical Background Anchoring Heuristic In Consumer Judgementioning
confidence: 86%
“…Numerous studies have demonstrated that in negotiations, first offers can act as anchors (e.g., Galinsky & Mussweiler, ; Galinsky, Ku, & Mussweiler, ; Loschelder, Stuppi, & Trötschel, ). Specifically, the outcomes of the negotiations are often biased in the direction of the first offers.…”
Section: Discussionmentioning
confidence: 99%